A coming boom in commercial shipping? The potential for rapid growth of noise from commercial ships by 2030. (November 2016) - Kaplan, Maxwell B.; Solomon, Susan
Abstract: Ocean noise levels are thought to be increasing as a result of major growth in global shipping activity, but data quantifying those changes are limited in space and time. As an alternative approach, this study examines the current and future maximum noise capacity of three segments of the global commercial shipping fleet: container ships, oil tankers, and bulk carriers. It shows that continued growth in the number of ships, the quantity of goods carried and the distances traveled could increase the maximum noise capacity of the global shipping fleet by up to a factor of 1.9 by 2030, with major growth in particular in the container and bulk carrier segments. Thus, in the absence of operational or manufacturing changes to such ships, the contribution of commercial shipping to ambient ocean noise levels can be expected to dramatically increase. Highlights: Commercial shipping has grown substantially over the last several decades. Increased ocean noise, which affects marine fauna, has been linked to this growth. Projections suggest that the fleet's noise capacity could nearly double by 2030. Mitigation measures could include operational or manufacturing changes.